A Media Analysis on the Current Situation of Nepalese Higher Education Policy Discourse - Devkota, Krishna Maya; Timilsena, Narayan Prasad (Innovative Research Journal, 2024)
The higher education system in Nepal faces multiple challenges, including low enrollment rates, political interference, outdated curricula, and poor alignment with labour market demands. The transition to federalism has further complicated governance and funding distribution, leading to disparities between institutions. Additionally, increasing numbers of students seek education abroad due to dissatisfaction with domestic opportunities. This study analyzes media discourse on higher education policies, particularly discussions hosted by Khabar Education.com and HISAN. Using qualitative analysis, the study examines issues such as governance inefficiencies, the impact of political influence, and curriculum-market misalignment. The findings highlight gaps in policy implementation, the need for structural reforms, and calls for depoliticization and modernization of higher education institutions. While recent policy efforts aim to address these concerns, their effectiveness remains uncertain. Without systemic reforms and strong governance, Nepal's higher education sector risks further decline.